Low-cost modular PV-battery microgrid emulator for testing of energy management algorithms - Gan, L; Riar, B; Lee, J; Howey, D (IEEE, 2017)
Within the context of microgrids, the need for a smart energy management system (EMS) has become increasingly important for users to maximise use of local energy generation and/or trade power effectively with the energy market if there is a grid connection. Many researchers have been developing algorithms to forecast the availability of renewable energy and load demands whilst optimising the energy flows within required constraints. Recently, control systems for peer-to-peer (P2P) microgrid architectures, which involve complex information and communication technologies, have also been given much attention. However, not all of these algorithms have been implemented and tested with real hardware, which may be attributed to the high cost involved and the safety concerns of a larger system. This paper describes the design, build and demonstration of a scaled down (100 W) P2P microgrid system to provide a low cost, modular, safe, portable testing environment for new EMS algorithms. The system nonetheless has realistic behaviour in terms of control interfaces, measurements and dynamics, and therefore provides a valuable insight into EMS implementation that cannot be obtained through simulations alone. In this work, three microgrid emulators were built and they can communicate with each other via TCP/IP, enabling development and demonstrations of distributed forecasting, control and optimisation algorithms.